2006
DOI: 10.3892/or.15.5.1373
|View full text |Cite
|
Sign up to set email alerts
|

Application of intrathecal trastuzumab (Herceptin™) for treatment of meningeal carcinomatosis in HER2-overexpressing metastatic breast cancer

Abstract: Leptomeningeal carcinomatosis represents a rare manifestation of metastatic breast cancer (MBC). A 39-yearold female presenting with HER2-overexpressing MBC and suffering from meningeal carcinomatosis was treated with the humanized antibody trastuzumab directed to HER2 by intrathecal administration. The patient was diagnosed with HER2-overexpressing stage III breast cancer in December 2003. In August 2004, the patient developed a singular intracerebral metastasis which was resected by neurosurgery followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 21 publications
0
59
0
1
Order By: Relevance
“…No clear clinical benefit could be documented, but there were no side effects other than mild local ventricle inflammation at autopsy [10]. This led others to administer IT trastuzumab [11][12][13][14][15][16][17]. Most patients experienced symptoms improvement and no adverse neurological effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No clear clinical benefit could be documented, but there were no side effects other than mild local ventricle inflammation at autopsy [10]. This led others to administer IT trastuzumab [11][12][13][14][15][16][17]. Most patients experienced symptoms improvement and no adverse neurological effects.…”
Section: Discussionmentioning
confidence: 99%
“…No consensus exists on the adequate dosing and frequency of IT trastuzumab, ranging from 5mg [10,17] to 100mg [14] dosing in a weekly [10,[13][14][15][16][17] to every three weeks [11,13] schedule, with 25mg…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that CM originating from lung cancer could be treated with gefitinib (25,10,7,18) and high-dose erlotinib (19) One study also suggested that trastuzumab may benefit some CM patients who had breast cancer (11). Recently, several authors reported successful treatment of meningeal carcinomatosis by intrathecal trastuzumab (17,22,26). Some studies indicate that radiotherapy (whole brain and involved-field irradiation of bulky spinal lesions) and chemotherapy (systemically or intrathecally applied methotrexate, thiotepa, and cytarabine) are both effective and may prolong survival from several weeks to 4-6 months in patients with CM (8, 4).…”
Section: Duan H Et Al: Carcinomatous Meningitis In the Chinese Populmentioning
confidence: 99%
“…14,17 The duration of disease control from the initiation of intrathecal trastuzumab ranged from 39 days to greater than 72 months, with 6 patients surviving greater than 5 months. [12][13][14][15][16][17] Interestingly, the patient who died at day 39 of intrathecal trastuzumab treatment died due to progression of visceral metastases and was considered to be in remission with regard to the leptomeningeal carcinomatosis. 10 Tumor cell counts were also found to be eliminated or substantially decreased in 4 of 5 patients.…”
Section: -17mentioning
confidence: 99%
“…Doses of trastuzumab ranged from 5 to 100 mg and were repeated after as little as 3 days in 1 report to as long as 3 weeks in others. 10,[12][13][14] The most common schedule was 20-30 mg weekly. All doses, including doses up to 100 mg, and schedules were well tolerated.…”
Section: -17mentioning
confidence: 99%